2012
DOI: 10.1021/jf303442u
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Protein Isolates from Caragana korshinskii Kom. Extracted by Three Different Methods

Abstract: Seeking cheap, sustainable protein sources greatly facilitates in alleviating the dependence upon expensive animal-based protein in many developing countries. Caragana korshinskii Kom. offers a good alternative feedstock because of its high-content of protein, low fertilizer and pesticide requirements, excellent stress (high salty and less water) tolerance, wide adaptability, etc. The functional properties of C. korshinskii Kom. protein isolates by three different extraction methods were investigated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…It is likely that during the slower extraction process, the stronger alkaline solutions are more effective in breaking down the structure of C. korshinskii Kom., thereby freeing more protein in the solvent, as suggested in previous research with distiller's grain (Bals et al, ). Furthermore, our previous study (Zhong et al, ) indicated that an increased alkalinity of the solvent would increase the protein solubility of C. korshinskii Kom. in aqueous solutions, also helping explain the higher protein yield due to increased NaOH concentration.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…It is likely that during the slower extraction process, the stronger alkaline solutions are more effective in breaking down the structure of C. korshinskii Kom., thereby freeing more protein in the solvent, as suggested in previous research with distiller's grain (Bals et al, ). Furthermore, our previous study (Zhong et al, ) indicated that an increased alkalinity of the solvent would increase the protein solubility of C. korshinskii Kom. in aqueous solutions, also helping explain the higher protein yield due to increased NaOH concentration.…”
Section: Resultsmentioning
confidence: 94%
“…exhibited good physiological characteristics. The in‐vitro digestion analysis indicated that they were even comparable with commercial soybean protein isolates (Zhong et al, ). However, valorization of the protein fraction is challenging in a biorefinery.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In-vitro digestibility of protein was determined as described by Groninger and Miller (1979) after incorporating the modification from Zhong et al (2012). Twenty milligram of pepsin was added to 700 mg of protein suspension having pH 1.5-2.0 (adjusted with 1 N HCl) and maintained at 37°C in a water-bath shaker.…”
Section: Molecular Weight (Mw) Determination By Gel Permeation Chromamentioning
confidence: 99%